Educational Attainment and Employment Outcome of Survivors of Pediatric CNS Tumors in Switzerland—A Report from the Swiss Childhood Cancer Survivor Study - Maria Otth; Gisela Michel; Nicolas U. Gerber; Ana S. Guerreiro Stücklin; André O. von Bueren; Katrin Scheinemann; on behalf of the Swiss Pediatric Oncology Group (SPOG) (Children, 2022)
Background: Childhood cancer survivors diagnosed with a central nervous system (CNS) tumor are at risk for educational and vocational challenges. This study compared educational attainment and employment outcome in survivors of CNS tumors to survivors of other malignancies. Methods: The questionnaire-based Swiss Childhood Cancer Survivor Study (SCCSS) included cancer patients diagnosed between 1976 and 2010, aged ≤20 years, who survived ≥5 years after diagnosis. We classified participants aged ≥16 years into three groups: CNS tumor and non-CNS malignancy with and without CNS-directed treatment. We analyzed educational attainment, employment outcome and special schooling. Subgroup analyses included survivors aged ≥25 years. Results: We analyzed 2154 survivors, including 329 (15%) CNS tumor survivors, 850 (40%) non-CNS tumor survivors with and 975 (45%) without CNS-directed treatment. Fewer CNS tumor survivors aged ≥25 years reached tertiary education (44%) compared to those without CNS-directed treatment (51%) but performed similar to survivors with CNS-directed treatment (42%). Among CNS tumor survivors, 36 (14%) received special schooling. Higher parental education was associated with higher levels in survivors. Employment outcome did not significantly differ between the three diagnostic groups. A higher proportion of CNS tumor survivors received disability pension or were unemployed. Conclusions: Our findings suggest that CNS tumor survivors need more time to achieve their highest educational level. This should influence clinical care of these survivors by offering vocational counseling.